Pengaruh Pendidikan Terhadap Kepuasan Kerja Melalui Kinerja Guru SMPI Miftahul Ulum Tambelangan Kabupaten Sampang - Fatthurosi Fatthurosi; Chamariyah Chamariyah; Wasis Budarto (Journal of Management and Creative Business, 2024)
Fatthurosi, 2023. The Effect of Education on Job Satisfaction Through Teacher Performance SMPI Miftahul Ulum Tambelangan Sampang Regency, Postgraduate Program, Wijaya Putra University. This type of research is explanatory, namely to test the hypothesis between hypothesized variables that will be tested. using a quantitative approach, the research sample was 42 respondents. In this study the data will be processed using SEM-PLS data analysis. The objectives of this study are: 1) To test and analyze whether education has a significant effect on job satisfaction. 2) To test and analyze whether education has a significant effect on teacher performance. 3) To test and analyze whether teacher performance has a significant effect on job satisfaction. 4) To test and analyze whether education has a significant indirect effect on job satisfaction mediated by teacher performance. The results showed that: 1) Education has a positive and significant effect on job satisfaction. This is evidenced by the original sample value of 0.174 and p-values of 0.045. 2) Education has a positive and significant effect on performance. This is evidenced by the original sample value of 0.335, and the p-values of 0.021. 3) Teacher performance has a positive and significant effect on job satisfaction. This is evidenced by the original sample value of 0.717 and p-values of 0.000. 4) Education has a significant positive effect on job satisfaction mediated by teacher performance. This is evidenced by the original sample value of 0.240 and the p-values of 0.002.